Singing streams: Describing freshwater soundscapes with the help of acoustic indices. Issue 11 (16th April 2020) - Decker, Emilia; Parker, Brett; Linke, Simon; Capon, Samantha; Sheldon, Fran
Abstract: Understanding soundscapes, that is, the totality of sounds within a location, helps to assess nature in a more holistic way, providing a novel approach to investigating ecosystems. To date, very few studies have investigated freshwater soundscapes in their entirety and none across a broad spatial scale. In this study, we recorded 12 freshwater streams in South East Queensland continuously for three days and calculated three acoustic indices for each minute in each stream. We then used principal component analysis of summary statistics for all three acoustic indices to investigate acoustic properties of each stream and spatial variation in their soundscapes. All streams had a unique soundscape with most exhibiting diurnal variation in acoustic patterns. Across these sites, we identified five distinct groups with similar acoustic characteristics. We found that we could use summary statistics of AIs to describe daytimes across streams as well. Most difference in stream soundscapes was observed during the daytime with significant variation in soundscapes both between hours and among sites. Synthesis and Application. We demonstrate how to characterize stream soundscapes by using simple summary statistics of complex acoustic indices. This technique allows simple and rapid investigation of streams with similar acoustic properties and the capacity to characterize them in a holistic and universal way. While we developed this technique for freshwater streams, it is also applicable to terrestrial and marine soundscapes. Abstract : Understanding soundscapes helps to assess nature in a holistic way and provides a novel approach to investigate ecosystems. In unprecedented spatial and temporal resolution, we recorded 12 freshwater streams in south‐east Queensland for multiple days, calculated three acoustic indices and used a principal component analysis to investigate acoustic properties of each stream. While all streams had a unique soundscape, we could also identified five distinct groups with similar acoustic characteristics across all sites, showing our technique allows a rapid investigation of stream soundscape.